Resource ecology of host-parasite interactions and evolution - (:unkn) unknown (My University, 2025)
Why do some parasites, like the common cold viruses, cause very little harm to their hosts, while others, like the plague bacterium, kill them very rapidly? There are, broadly speaking, two approaches to answer this question. On the one hand, we try to understand the mechanistic basis of the host-parasite interaction: its molecular and cellular biology and its physiology. On the other hand, we try to understand the evolutionary pressures shaping the interaction. Most of our evolutionary ideas are formulated within a framework assuming that increased virulence is the unavoidable consequence of a higher rate of the parasite’s transmission, i.e. that there is a trade-off between virulence and rate of transmission. Each approach has developed more or less independently of the other, leaving each somewhat unsatisfactory and preventing a complete picture of host-parasite evolution. With the work of this proposal, I will try to give a mechanistic basis to the evolutionary ideas underlying host-parasite interactions by considering them in the context of resource ecology. This takes into account a fundamental aspect of parasites that, however, is generally ignored: that they steal resources from their host to support their own development. The approach asks how the availability of the host’s resources constrains its own and its parasite’s growth, and how their evolutionary strategies of both change according to both partner’s resource-based constraints. The project deals with the microsporidian Vavraia culicis and its host, the mosquito Aedes aegypti. Developing mathematical theory in close contact with experimental studies that test the model’s assumptions and predictions, I will approach the problem in three steps. First, I will adapt models of individual development to show how the availability of resources (and thus energy) constrains the mosquito’s growth. This environmental constraint, in turn, will influence the developmental strategy used by the mosquito to achieve its reproductive success. Explaining variation of such strategies is the aim of life-history theory. This first step is thus essentially an attempt to introduce mechanistic descriptions of individual growth into life-history theory. Second, as the parasite’s growth depends on the resources it obtains from its host, it will affect the host’s energy budget; the model of individual growth will be modified accordingly. This will enable me to answer two sets of questions. (i) How do the host’s resources affect the parasite’s growth and epidemiological parameters associated with parasite load: its transmission rate and virulence? (ii) How does the parasite affect the host’s growth and thus its optimal life-history? Third, while the parasite’s virulence and transmission are constrained by the growth within its host, its evolution is determined by its epidemiological dynamics. I will therefore combine the models linking resource ecology to within-host dynamics of the parasite with models describing its epidemiology. This gives the possibility to reach the goal of the project: to describe the evolution of the parasite’s virulence as a function of its host’s resources.
Keywords: resource ecology; virulence; parasite evolution; host-parasite interactions